IMPLEMENTATION OF MICRO AND SMALL BUSINESS LICENSE SERVICES THROUGH OSS (ONLINE SINGLE SUBMISSION) AT THE PUBLIC SERVICES MAL OFFICE OF BARRU DISTRICT - Dian Pratiwi; Nada Carolina (P3M Stia Al Gazali Barru and Meraja media, 2021)
Copyright (c) 2021 Meraja journal